A detailed perspective of water resource management in a dry and water scarce country: The case in Kuwait - Tariq, Muhammad Atiq Ur Rehman; Alotaibi, Rabeeah; Weththasinghe, Kumudu Kaushalya; Rajabi, Zohreh (Frontiers in Environmental Science, 2022)
Kuwait is an arid and dry country suffering from severe water scarcity with 165 m3/year/capita consumption rates, which is one of the highest in the world. The main sources of freshwater are desalination, brackish groundwater, and recycling wastewater. Desalination is the main source to produce 61% of freshwater for the drinking, agriculture, and water dependent industries. Several other measures related to rainfall drainage system and water supply network are also em-ployed. The country spends a significant amount on direct water supply and importing food and subsidizes about 92% of production costs, which is a burden on the country’s economy. The de-pendency on imported food items is considered a main political and security concern in the nation. Multiple government organizations with the enforcement of several legal frameworks over-see the long-term and acute water related issues. Regional neighbors also face the similar climatic conditions as of Kuwait and water shortage. Although desalination is the main source of fresh-water, the stress can be reduced by opting for water conservation. Other small countries with similar conditions also consider cultivation of water efficient crops. Due to its small size and dry arid climate, the future is challenging, and Kuwait must invest on modern, innovative, and effective solutions to ensures the sustainability of its freshwater resources.